Beauty. (26th October 2022) - Tate, Shirley Anne
Abstract: Beauty is not race neutral. It is a racialized category/ perception which emerged through centuries of European colonization, Indigenous genocide, African/Black enslavement and indenture resulting in an aesthetic hierarchy with Blackness at the bottom. The coloniality of aesthetics means that still today hair perceived as Black in texture and styling and darker skin on African descent bodies are the repositories of anti‐Blackness. However, Black women, children and men continue to fight back by (re)creating Black antiracist aesthetics focused on valorizing Black skin and hair.